Importance des roles dans la vie: qualities psychometriques de la version francaise du Life Role Salience Scale - Lachance, Lise; Tétreau, Bernard (Canadian Journal of Counselling and Psychotherapy, 2007)
The Life Role Salience Scale is a most valuable tool for assessing the relative importance of four major roles (occupational, parental, marital, homecare) in a person's self-definition and willingness to commit personal resources in order to ensure success in these roles or to develop them. In all, 40 items were used to measure these two dimensions for each role. The study outlines the psychometric factors of the French version of the LRSS prepared from a sample of 468 participants and compares these factors with those in the original American version. The alpha coefficients were found to be quite adequate. The results of factor analyses and correlations between the scales seem to support a four-factor solution corresponding to each role. Some applications are suggested for the practice of counselling.